IUBIREA – MIJLOC DE APROFUNDARE A LIBERTĂȚII, SOLIDARITĂȚII ȘI UNITĂȚII DINTRE OAMENI (Journal for Freedom of Conscience (Jurnalul Libertății de Conștiință), 2022)
Love – A Means of Understanding Freedom, Solidarity and Unity Between PeopleThe essence of perfection consists in love, because love is the greatest virtue, perfection and perfection engine itself (only God is love!). Forward completely, you save yourself realizing that God is united to every human being, that he by the grace of his Spirit assisting you continually, giving you grace upon grace is there for you and obviously when immerse yourself in sin as a loving father as to give you better help to get up and (re) take the perfection. Not only St. Paul, but St. John showed us that the way of perfection through neighbour by supporting and working with him. Just as Christianity is not a philosophical speculation or a simple way, it is an event, a relationship is the way of perfection that go with God (grace) to a deeper and greater union with God.